Feasibility of using WeChat to improve infant and young child feeding in rural areas in China: A mixed quantitative and qualitative study. - Qiong Wu; Yiwen Huang; Michelle Helena van Velthoven; Wei Wang; Suying Chang; Yanfeng Zhang (PLoS ONE)
Background Appropriate infant and young child feeding practices are the basis for child nutrition. In China, WeChat is gradually changing the channels through which people receive information. The paper aims to explore the feasibility of using WeChat to improve infant and young child feeding in rural China. Methods A mixed-methods study was carried out in Huzhu County, Qinghai province, China. We conducted two cross-sectional surveys with children aged 6-23 months and their caregivers in 2012 (N = 1804) and 2018 (N = 754), respectively. Quantitative data were collected on feeding knowledge and practices, caregiver's use of smartphones and WeChat. Qualitative data were from 33 semi-structured interviews with pregnant women and mothers. In addition, we developed a WeChat feeding health education platform and asked women about their experiences with using it. Results In both cross-sectional surveys, less than 10% of caregivers knew that breastfeeding can be continued up to two years, less than 50% knew the accurate duration of exclusive breastfeeding, and only around 20% knew meat can be given to children from the age of 6-8 months. Similarly, the feeding practices were suboptimal and most key infant feeding practices did not change over the years. Only around 30% of caregivers ever received feeding information during pregnancy or after delivery in both surveys. Around 50% of caregivers received information from their relatives and friends, followed by 30% from health facilities and communities. More than 80% of mothers were currently using both a smartphone and the WeChat app, and 75.4% of them were willing to receive feeding information from WeChat official accounts. The WeChat feeding health education platform developed by our study team was generally well accepted by women. Conclusions There was an absence of accurate information sources on infant feeding and child nutrition. WeChat could be a potential way to deliver infant feeding recommendations to pregnant women and mothers in rural China. Trial registration ChiCTR-PRC-11001446 (The controlled intervention trial for complementary food supplements "Yingyangbao"); ChiCTR1800017364 (the randomized controlled trial for WeChat).